Polymorphisms of genes coding for ghrelin and its receptor in relation to colorectal cancer risk: a two-step gene-wide case-control study - Campa, Daniele; Pardini, Barbara; Naccarati, Alessio; Vodickova, Ludmila; Novotny, Jan; Steinke, Verena; Rahner, Nils; Holinski-Feder, Elke; Morak, Monika; Schackert, Hans K; Görgens, Heike; Kötting, Judith; et al. (BMC gastroenterology, 2010)
BACKGROUND: Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor (GHSR), has two major functions: the stimulation of the growth hormone production and the stimulation of food intake. Accumulating evidence also indicates a role of ghrelin in cancer development. METHODS: We conducted a case-control study to examine the association of common genetic variants in the genes coding for ghrelin (GHRL) and its receptor (GHSR) with colorectal cancer risk. Pairwise tagging was used to select the 11 polymorphisms included in the study. The selected polymorphisms were genotyped in 680 cases and 593 controls from the Czech Republic. RESULTS: We found two SNPs associated with lower risk of colorectal cancer, namely SNPs rs27647 and rs35683. We replicated the two hits, in additional 569 cases and 726 controls from Germany. CONCLUSION: A joint analysis of the two populations indicated that the T allele of rs27647 SNP exerted a protective borderline effect (Ptrend = 0.004).
Keywords: alely; Humans; lidé středního věku; Receptors, Ghrelin; dítě; polymorfismus genetický; Child; Female; rizikové faktory; mladý dospělý; dospělí; Aged; Alleles; senioři; lidé; Germany; Polymorphism, Genetic; Německo; ghrelin; Adult; receptory ghrelinu; ženské pohlaví; kolorektální nádory; Ghrelin; Male; Middle Aged; Retrospective Studies; Adolescent; genetická predispozice k nemoci; incidence; Genetic Predisposition to Disease; Czech Republic; Incidence; Aged, 80 and over; Young Adult; senioři nad 80 let; retrospektivní studie; Česká republika; DNA nádorová; mužské pohlaví; DNA, Neoplasm; Colorectal Neoplasms; mladiství; Risk Factors